1980
DOI: 10.1007/bf00433057
|View full text |Cite
|
Sign up to set email alerts
|

Effects of apomorphine on elicited and operant pecking in pigeons

Abstract: The effects of apomorphine (0.001--32.0 mg/kg) on elicited and operant pecking were studied in pigeons. Elicited pecking was measured in a 1-h observation test. Apomorphine caused dose-related increases in the pecking elicited by the drug in all the subjects, with maximal responding at 3.2 mg/kg. In contrast, operant responding on a multiple, 5 min fixed interval, 30 response fixed-ratio schedule revealed individual differences in sensitivity to the drug. A dose of 0.32 mg/kg eliminated key pecking in fixed-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
1

Year Published

1983
1983
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
3
1
Order By: Relevance
“…This is in contrast to the previous finding that the direct dopamine agonist apomorphine elicits drug-induced pecking in pigeons [e.g., 34]. Furthermore, Pinkston and Branch [22] observed a dose-dependent decrease in preening behavior in pigeons that received IM cocaine.…”
Section: Introductioncontrasting
confidence: 99%
“…This is in contrast to the previous finding that the direct dopamine agonist apomorphine elicits drug-induced pecking in pigeons [e.g., 34]. Furthermore, Pinkston and Branch [22] observed a dose-dependent decrease in preening behavior in pigeons that received IM cocaine.…”
Section: Introductioncontrasting
confidence: 99%
“…First, we found that cocaine did not affect spontaneous pecking at the doses tested here; such data are in line with the observation that another indirect monoamine agonist, d ‐amphetamine, does not generally affect pecking, or does so only weakly (Goodman, 1981). In some sense, it is surprising that cocaine and amphetamine have such a weak effect on pecking because the direct dopamine agonist apomorphine is known to stimulate pecking in pigeons (e.g., Abelson & Woods, 1980; Acerbo & Delius, 2004; Pinkston, Madden, & Fowler, 2008). Such differences may be due to cocaine and amphetamine's action on multiple neurotransmitter systems.…”
Section: Discussionmentioning
confidence: 99%
“…When given to pigeons, the nonselective, direct‐acting dopamine agonist apomorphine elicits prolonged bouts of pecking (Abelson & Woods, 1980; Goodman, 1981; Lindenblatt & Delius, 1988; Pinkston, Madden, & Fowler, 2008). Pecking emerges within minutes of administration and lasts for about an hour; the behavioral response is robust, several thousand pecks may be recorded following a single administration.…”
mentioning
confidence: 99%
“…As the research cited above seems to have established that the drug does not enhance food capture and ingestion, the present study was an analysis of the effects of apomorphine on operant procurement behavior. Previous work has shown that when the apomorphine-elicited pecks are directed at the operandum, operant response rate increases; when these pecks are directed at other parts of the apparatus, rate decreases (Abelson & Woods, 1980). It is likely such differences are topographical only and depend on the animal's individual history; for example, it has been shown that the characteristics of the operandum (key or treadle) can alter the topography of elicited pecking (Graeff & De Oliveira, 1975).…”
mentioning
confidence: 99%